Distribution and some biological features of Arctodiaptomus (Rhabdodiaptomus) bacillifer (Koelbel, 1885) (Copepoda, Calanoida) in Kazakhstan - E.g., Krupa; A., Kenzheyeva (Zootaxa, 2025)
Based on the males and females’ morphology and own long-term data, the freshwater diaptomid copepod Arctodiaptomus (Rhabdodiaptomus) bacillifer (Koelbel, 1885) presence was confirmed at three localities of Kazakhstan: the ultra-fresh mountain lakes Markakol (Eastern Kazakhstan) and Upper Kolsay, and a small lake located in the floodplain of the Aksu River (Southeastern Kazakhstan). A. (R.) bacillifer is known from various regions of the world not only as an inhabitant of ultra-fresh and fresh waters, with a total dissolved solids of 0.08–0.81 g/dm3, but also in salt waterbodies (up to 58.1 g/dm3). The reasons for the contradictory information on the distribution and biology of A. (R.) bacillifer in Kazakhstan and other regions are discussed. A comparative analysis of the key identifying features of its morphologically close congeners A. (R.) bacillifer, A. (R.) acutilobatus (Sars, 1903), and A. (R.) salinus (Daday, 1885), which are often mistakenly identified, is provided. The necessity of critical analysis of data on the wide distribution of A. (R.) bacillifer in mineralized waterbodies of different regions of the world is emphasized, since A. (R.) bacillifer, in addition to A. (R.) acutilobatus, A. (R.) salinus, is mixed with other species of the subgenus, in particular, with “alpinus” and “rectispinosus”. The absence of A. (R.) bacillifer in the optimal gradient of water mineralization is likely caused by competitive relationships with other species of calanoid crustaceans, most often with Acanthodiaptomus denticornis (Wierzejski, 1887) and Arctodiaptomus (Rhabdodiaptomus) spinosus (Daday, 1891).